Um estudo do envolvimento e das atitudes do consumidor de plantas medicinais na cidade de Uberlândia MG - Rezende, Rejane Carmo (2011)
The actual work presents the study of Uberlandenses consuming behavior regarding medicinal plants. This work has as its general objective measure the medicinal plants consumers involvement and attitude within Uberlandia MG. It also has a specific objective as to evaluate the trustworthiness of the scales for the products containing medicinal plants, to determine the existing relation among the involvement and the attitude of the medicinal plants consumer and establish the existing involvement relation and the components of the frequent attitude of the product use, product knowledge, levels of education, gender, age, family income, marital status and health condition (healthy or unhealthy).For such purposes, firstly a theoretical study was performed and a quantitative field study was immediately done. In the theoretical research the work pointed a medicinal plants consumption study, the consumer behavior and purchase process and the consumer involvement and attitude. This research consisted of the data collecting through some self completion questionnaires and this data was tabulated and processed in SPSS statistical software (Statistical Package for the Social Sciences) version 15.0.This work has reached the proposed objectives considering that the involvement and attitude measurement showed that the uberlandenses medicinal plants consumers possess from moderate to high involvement and attitude, presenting this way a high involvement for the Relevance and Risk Probability factors and high attitude for the cognitive component. It was also evidenced in this work that the involvement and the attitude of the consumer relate to each other in a positive way, therefore, the more it has some involvement the more one has favorable attitudes (or vice versa).Through the social demographical factors related to the involvement and attitude evidenced, it is concluded that the advertising can be focused towards the adult public who is already frequently using these products and would like some information about the product containing medicinal plants. This group might give emphasis to the products which offer wellbeing and aesthetic. This research provides subsidies which can be used by the professionals of marketing companies located in Uberlândia-MG whom produce and/or sell products containing medicinal plants. Furthermore it contributes for the consumer behavior and also these plants consumer behavior studies.